Multifaceted roles of TRIM38 in innate immune and inflammatory responses - Hu, Ming-Ming (Cell Mol Immunol, 2017)
The tripartite motif-containing (TRIM) proteins represent the largest E3 ubiquitin ligase family. The multifaceted roles of TRIM38 in innate immunity and inflammation have been intensively investigated in recent years. TRIM38 is essential for cytosolic RNA or DNA sensor-mediated innate immune responses to both RNA and DNA viruses, while negatively regulating TLR3/4- and TNF/IL-1β-triggered inflammatory responses. In these processes, TRIM38 acts as an E3 ubiquitin or SUMO ligase, which targets key cellular signaling components, or as an enzymatic activity-independent regulator. This review summarizes recent advances that highlight the critical roles of TRIM38 in the regulation of proper innate immune and inflammatory responses.